2021
DOI: 10.1007/s13280-021-01691-y
|View full text |Cite
|
Sign up to set email alerts
|

Guiding restoration of riparian ecosystems degraded by plant invasions: Insights from a complex social-ecological system in the Global South

Abstract: Restoring riparian ecosystems in human-dominated landscapes requires attention to complexity, and consideration of diverse drivers, social actors, and contexts. Addressing a Global North bias, this case study uses a mixed-method approach, integrating historical data, remote sensing techniques and stakeholder perceptions to guide restoration of a river in the Western Cape, South Africa. An analysis of aerial photographs of the riparian zone from 1953 to 2016 revealed that although anthropogenic land conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The NBS that were planned, under consideration or implemente included a planned river opening with landscape alteration and leach erside park and constructed wetlands, water ponds integrated into a The NBS that were planned, under consideration or implemented in the case studies included a planned river opening with landscape alteration and leachate treatment, a riverside park and constructed wetlands, water ponds integrated into a city park, the restoration and conservation of degraded land and native vegetation, respectively, establishing tree gardens and riparian rehabilitation. Detailed descriptions of each case study can be found in previous publications [4,[23][24][25][26][27][28] and in NATWIP project case study briefs (http://www.natwip.solutions/Pages/publications.html (accessed on 7 January 2023)). A description of the case studies can be found below.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The NBS that were planned, under consideration or implemente included a planned river opening with landscape alteration and leach erside park and constructed wetlands, water ponds integrated into a The NBS that were planned, under consideration or implemented in the case studies included a planned river opening with landscape alteration and leachate treatment, a riverside park and constructed wetlands, water ponds integrated into a city park, the restoration and conservation of degraded land and native vegetation, respectively, establishing tree gardens and riparian rehabilitation. Detailed descriptions of each case study can be found in previous publications [4,[23][24][25][26][27][28] and in NATWIP project case study briefs (http://www.natwip.solutions/Pages/publications.html (accessed on 7 January 2023)). A description of the case studies can be found below.…”
Section: Case Studiesmentioning
confidence: 99%
“…The NBS that has been implemented to manage the infestation includes clearing invasive alien trees from the riparian zone and active rehabilitation via planting indigenous riparian vegetation [24]. Running parallel to the NBS was a scheme to engage the community, where employment opportunities were created through this rehabilitation programme, a recycling scheme was set up and a native tree growing program was trialled [27].…”
Section: South Africa-dwars Rivermentioning
confidence: 99%
“…Reliable invasive species distribution maps are important for targeting management of infestations, modelling future invasion risk [12], assisting with policy decisions, strategic allocation of funding, effective implementation of control programmes [13][14][15][16] and planning for ecological restoration [17,18]. Traditional mapping of weeds is time-consuming, rapidly outdated, labor-intensive and expensive, and relying heavily on field-based surveys has associated challenges such as dealing with inaccessible and expansive areas [19].…”
Section: Introductionmentioning
confidence: 99%